Analisis Kapasitas Sistem Saluran Drainase (Studi Kasus Drainase Jalan Siliwangi Kota Batam) - Winardo, Rico; Indrastuti, Indrastuti (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
Batam City is one of the cities in the Riau Archipelago Province with the largest population growth. Along with the development of the city and the increase in population, the need for public facilities and infrastructures also need to be developed, such as on Jalan Siliwangi. Jalan Siliwangi is one of the roads in the Batu Besar area, Nongsa sub-district in Batam city which is experiencing problems with the drainage system. Drainage is a technical measure to prevent excess water due to high rainfall intensity and drain it to a collection point. Rainfall intensity is a condition where rain is highly concentrated and occurs at a certain time. This research was conducted to know whether the Siliwangi Road drainage channel is working optimally so that it can accommodate water during high rainfall. This analysis uses the Gumbel method using extreme values. The extreme values of rain intensity that will be taken into account are several return periods, namely 2, 5, 10, 25, 50, and 100 years. The calculated channel discharge using location data is Q = 0.5637 m3/second, while the planned discharge calculated using rainfall data is Q = 2.064 m3/second. From the results of the analysis of the dimensions of the planned canal found in the field, it does not meet the design capacity so waterlogging occurs, where the height and width of the planning canal are larger. By using the frequency distribution formula of the Gumbel and Log Person Type III methods for the calculation and application of parameters related to the analysis of average data, standard deviation, and determining the frequency of rainfall for the T-year return period in the discussion above, it can be concluded that the drainage channel on Jalan Siliwangi Batam unable to prevent inundation or flooding during high rainfall.